Vitamin D Intake and Factors Associated With Self-Reported Vitamin D Deficiency Among US Adults: A 2021 Cross-Sectional Study - Andrade, Jeanette M.; Grandoff, Philip G.; Schneider, Sydney T. (Frontiers in Nutrition, 2022)
Vitamin D deficiency is a global issue that may be attributed to various factors such as dietary habits, sun exposure, age, race and chronic conditions. The purpose of this study was to determine the relationship between vitamin D intake from food/supplements and factors that may be associated with self-reported vitamin D deficiency among US adults. A cross-sectional online study was conducted among 1637 adults using a 38-item questionnaire. Frequency counts and percentages were tabulated and a multiple linear regression was performed. Statistical significance was determined at p<0.05. A majority of participants were never informed they were vitamin D deficient (60%), regardless of vitamin D status, 36.6% took a vitamin D supplement at least once daily, and consumed an average of 347.05 ±307.8 IUs of vitamin D through foods/beverages. The multivariate linear regression showed significant positive correlations for chronic kidney disease (0.05, CI 95% 0.01-0.40; p=0.04), depression (0.07, CI 95% 0.03-0.17; p<0.001), diabetes (0.06, CI 95% 0.02-0.23; p=0.02), and vitamin D supplement use (0.17, CI 95% 0.05-0.08; p<0.001) on vitamin D deficiency status. Significant negative correlations were discovered with age (-0.08, CI 95% -0.06 to -0.01; p=0.01) and sun exposure (-0.09, CI 95% -0.04 to –0.01; p<0.001) on vitamin D deficiency status. No relationships were seen with vitamin D intake from foods/beverages on vitamin D deficiency status. Overall, consumption of vitamin D intake from foods/beverages were below recommendations and relationships were seen with chronic diseases and vitamin D deficiency. Future focus should be on educating individuals about consuming and preparing foods naturally high in vitamin D to reduce the prevalence of vitamin D deficiency.